Abordagem das dificuldades para o ensino e implementação da metodologia Building Information Modeling (BIM) com foco em engenharia - ALMEIDA, Paulo Victor Vieira de (2025)
This article sought to identify the main difficulties encountered by students when using BIM software to design an architectural project, making a comparison with CAD technology. Data was collected by applying two questionnaires asking about Revit and AutoCAD and their respective technologies. The questionnaires were used to analyze the main difficulties encountered by students in migrating from CAD to BIM technology and the difficulties they face when designing projects. It was found that the main difficulties are related to the lack of practicality with the program. Another point that can be seen is that the vast majority of students would adopt BIM software. This problem can be solved by implementing this technology through subjects in the undergraduate curriculum and incentives to use the tool in the learning process.